1987
DOI: 10.1243/emed_jour_1987_016_024_02
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Ceramics in Prosthetic Heart Valves

Abstract: A survey is carried out of how various ceramics have been used or considered as materials for prosthetic heartvalves. The ceramics include pyrolitic carbon, titanium dioxide, porous and fully dense alumina, and single crystal alumina. Particular attention is paid to the ability of some types of alumina to support a stable tissue covering which then camouflages them from further interactions with the blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Furthermore, in the histological evaluation of other parameters such as pseudo-rosette formation, Müller cell hypertrophy, disruption of the normal retinal pigment epithelium (RPE), monolayer and RPE migration, DLC scored better than AAO. While excellent biocompatibility for AAO-coated devices in high blood-throughput applications was reported in the literature [11][12][13][14][15][16][17][18], our implantation studies in the subretinal space indicate that AAO is more detrimental to the surrounding inner and outer retinal tissue than DLC. When considering biocompatibility distinctions must be made about the target tissue.…”
Section: Biocompatibilitymentioning
confidence: 58%
See 1 more Smart Citation
“…Furthermore, in the histological evaluation of other parameters such as pseudo-rosette formation, Müller cell hypertrophy, disruption of the normal retinal pigment epithelium (RPE), monolayer and RPE migration, DLC scored better than AAO. While excellent biocompatibility for AAO-coated devices in high blood-throughput applications was reported in the literature [11][12][13][14][15][16][17][18], our implantation studies in the subretinal space indicate that AAO is more detrimental to the surrounding inner and outer retinal tissue than DLC. When considering biocompatibility distinctions must be made about the target tissue.…”
Section: Biocompatibilitymentioning
confidence: 58%
“…Devices coated with AAO have been tested in high blood-throughput environments such as heart valves, and significant high blood compatibility was reported [13][14][15]. The blood interaction of AAO was studied comprehensively by Yuhta, who reported that sputter-deposited aluminum oxide produces a durable and blood-compatible coating.…”
Section: Introductionmentioning
confidence: 99%